An internal encapsulating layer for efficient, stable, repairable and low-lead-leakage perovskite solar cells. Issue 9 (2nd August 2022) - Xu, Dongdong; Mai, Runsheng; Jiang, Yue; Chen, Cong; Wang, Ru; Xu, Zhengjie; Kempa, Krzysztof; Zhou, Guofu; Liu, Jun-Ming; Gao, Jinwei
Abstract : The in situ synthesis of a cross-linked polymer (Spiro-NPU ) as an internal encapsulating layer (IEL) supports the development of efficient, stable, repairable, and low-lead-leakage perovskite solar cells. Abstract : Perovskite solar cells (PSCs) have demonstrated remarkable progress, showing high power conversion efficiencies (PCEs) and low cost. However, there is still huge room for improvement in terms of long-term stability, repairability, and lead toxicity reduction before large-scale industrialization can start. Here, we propose an internal encapsulating layer (IEL) based on an in situ cross-linked insoluble polymer (Spiro-NPU ) with matched energy levels, good electrical conductivity, and matched hole mobility. While the insertion of Spiro-NPU significantly enhanced the photovoltaic performance, with highest PCEs of 23.26% on a rigid substrate and about 20% for flexible devices, most importantly, the IEL strongly enhanced the moisture/thermal stability and repairability of the PSCs. No PCE decay was observed after 3000 h of aging in air at 60% relative humidity (RH); over 90% of the initial efficiency was maintained after 500 h of aging at 85% RH and 25 °C (or at 55% RH and 85 °C); and 97% of the initial PCE was retained after operating at the maximum power point (MPP) under 1 sun illumination (∼50 °C in N2 ) for 200 h without any external encapsulation. In addition, the photovoltaic-inactive hydrated phase of the perovskite film obtained after one month of aging (85% RH at 25 °C) can be recovered back into the photovoltaic-active black phase after annealing or irradiation at 1 sun, and the corresponding PSCs also show this repairability. Furthermore, our IEL exhibits lead blocking capabilities, paving the way to a promising strategy aimed at stable, efficient, and safe PSCs.